O direito à cidade em uma perspectiva do consumo segundo as famílias moradoras pós mudança habitacional : o caso do PAC Beberibe em Recife - ROCHA, Stella D'Angelis Rodrigues (2016)
This paper chiefly aims at understanding the perception that recipient families entitled to the Housing State Program under PAC Beberibe have on experiencing their right to the city, taking into account the consumption perspective of collective use-driven goods. Besides the economic reasoning, consumption can be also construed as a social distinction factor, and also as political expression, when reasoned as a purpose of grassroots struggle for the equal access right to the ensemble of goods and services made available within the urban background. The perspective of the said consumption construing further enhances the studies dedicated to social inclusion process, in particular, when dealt with the urban setting and upon taking the city as a product of human labour, placed within a capitalist environment that brings together not only the physical structural dimension, but also the cultural, symbolic and the political dimension underneath the daily life. Aiming to meet the purposes of the said survey, the paper hereof turned out to be an exploratory, quality-led research. The empirical background of this paper comprised the families who have left the wretched dwellings in the banks of Beberibe River and currently live in council housings built according with Beberibe Basin’s Integrated Sanitation Programme (PAC Beberibe), carried out in the municipality of Recife, State of Pernambuco. Hence, upon the sample selection based on the snowball sampling technique, the empiric contribution to the speech analysis was employed as related to the French line to guide the search for the meaning given to the right to the city as experienced by the recipient families through their own descriptions. Among the outcomes thus achieved, it should be stressed that it is becomes indispensable that social housingoriented public policies are built upon the housing concept in a broader sense than its physical infrastructure, by encompassing the home feeling awareness and the entitlement to other social rights to the family, including the access to mass consumption goods and services and the actual involvement at the urban development, based upon the adoption of the citizenship status.